Angiotensin II Promotes Osteocyte RANKL Expression via AT1R Activation - Jiayi Ren; Aseel Marahleh; Jinghan Ma; Fumitoshi Ohori; Takahiro Noguchi; Ziqiu Fan; Jin Hu; Kohei Narita; Angyi Lin; Hideki Kitaura (Biomedicines)
Background/Objective: Osteocytes are the most abundant cell type in the skeleton, with key endocrine functions, particularly in regulating osteoblast and osteoclast activity to maintain bone quality. Angiotensin II (Ang II), a critical component of the renin–angiotensin–aldosterone system, is well-known for its role in vasoconstriction during hypertension. Beyond its cardiovascular functions, Ang II participates in various biological processes, including bone metabolism. While its influence on osteoblast proliferation, differentiation, and osteoclastogenesis has been documented, its effects on osteocytes remain unexplored. This study hypothesized that Ang II enhances the osteoclastogenic activity of osteocytes. Methods: Mouse calvariae were cultured ex vivo in an Ang II-containing medium, analyzed via immunohistochemistry, and evaluated for osteoclastogenic gene expression through real-time PCR. Western blotting was employed to assess protein levels and signaling pathway activation in the MLO-Y4 osteocytic cell line in vitro. Results: Ang II significantly increased the expression of receptor activator of nuclear factor κB ligand (RANKL) and macrophage colony-stimulating factor (M-CSF). These effects were abrogated by azilsartan, a blocker targeting Ang II type 1 receptors (AT1R). p38 and ERK1/2 in the MAPK pathway were also activated by Ang II. Conclusions: Ang II enhances osteocyte-mediated osteoclastogenesis via AT1R activation, highlighting its potential as a therapeutic target for bone diseases.